2020
DOI: 10.1089/met.2019.0114
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Serum Uric Acid Level and the Severity of Coronary Artery Disease in a Retrospective Study of China Nondialysis CKD Patients

Abstract: Introduction: Hyperuricemia has been associated with increased cardiovascular events in the general population. However, the role of serum uric acid (SUA) level on the severity of coronary artery stenosis (CAS) in nondialysis chronic kidney disease (CKD) patients is obscure. Methods: We implement a retrospective cohort study of 734 patients diagnosed with stage 3-5 CKD. All selected patients underwent coronary artery angiography. The associations of SUA with the present, and severity of coronary artery disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…46 Recently, it has been reported that serum uric acid levels may serve as a predictor of the severity of coronary artery stenosis in nondialysis CKD patients with coronary disease. 47 In agreement, in our data we observed a significant unadjusted relationship between high serum uric acid and CAD occurrence. Furthermore, in this study coronary disease was significantly associated with vascular stiffness, low rate of renal function, and albuminuria.…”
Section: Discussionsupporting
confidence: 92%
“…46 Recently, it has been reported that serum uric acid levels may serve as a predictor of the severity of coronary artery stenosis in nondialysis CKD patients with coronary disease. 47 In agreement, in our data we observed a significant unadjusted relationship between high serum uric acid and CAD occurrence. Furthermore, in this study coronary disease was significantly associated with vascular stiffness, low rate of renal function, and albuminuria.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies by Rahmani et al and Johnson et al, the authors noted a positive association between serum uric acid levels and the severity of CAD [ 12 , 13 ], similar to our study which also demonstrated a positive association. However, new research revealed that uric acid levels were a less accurate predictor of CAD severity [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…In ESRD patients on peritoneal dialysis, thrombocytosis also appeared to be relevant to the severity of CAD and peripheral arterial disease assessed by Severity Index (24). A retrospective study in the Chinese non-dialysis patients with CKD concluded that serum uric acid level as a category variable was an independent risk factor for severe arterial stenosis and was associated with the risk of CAD as a continuous variable (25). Disturbance of the mineral metabolism particularly for biomarkers, such as serum calcium and phosphorus, can multiple cardiovascular disease and vascular calcification.…”
Section: Discussionmentioning
confidence: 99%